2016
DOI: 10.1039/c5sc02311d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipid peroxidation on membrane permeability of cancer and normal cells subjected to oxidative stress

Abstract: Molecular dynamics simulations suggest that the cholesterol-induced stability of lipid membranes during lipid peroxidation offers an explanation for the observed selectivity of plasma treatments towards cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
259
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(296 citation statements)
references
References 70 publications
16
259
1
1
Order By: Relevance
“…Initially, plasma membrane-anchored GC-PEG-PpIX molecules activated photoinduced cell membrane damage, causing compromised membrane integrity. According to the literature, ROS can cause peroxidation of membrane lipids which consequently leads to increased membrane permeability and even pore formation [74]. Therefore, extracellular GC-PEG-PpIX NPs were readily internalized into cells and interacted with cytoplasmic membrane-containing organelles to promote cell destruction upon irradiation, which further led to self-enhanced cell influx of PDT agents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Initially, plasma membrane-anchored GC-PEG-PpIX molecules activated photoinduced cell membrane damage, causing compromised membrane integrity. According to the literature, ROS can cause peroxidation of membrane lipids which consequently leads to increased membrane permeability and even pore formation [74]. Therefore, extracellular GC-PEG-PpIX NPs were readily internalized into cells and interacted with cytoplasmic membrane-containing organelles to promote cell destruction upon irradiation, which further led to self-enhanced cell influx of PDT agents.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Our findings also suggest that by controlling α-toc concentration, the stability of biological membranes can be increased. This understanding of how α-tocs affect oxidized membranes is likely to be beneficial for designing new molecules to protect, e.g., skin, against aging 55,56 and in plasma treatment of cancer 48 .…”
Section: Figure 2 the Time Evolution Of The Position Of The Hydroxylmentioning
confidence: 99%
“…The effects these molecules on biological membranes are similar and that has been suggested for being responsible for the observed increase of bilayer thickness and lipid tail order. 25,48,49 Moreover, Issack et al 50 have shown that the free-energy barrier for transferring a water molecule to the center of the bilayer was increased by 6 kJ/mol when 41 mol% cholesterol was present in a DPPC bilayer. This observed significant increase of the free energy barrier to transfer water through bilayer with the presence of cholesterol results in a decrease in water permeability.…”
mentioning
confidence: 99%
“…The effects of gamma irradiation on the overall chemical structure of liposomes have been extensively investigated to understand its influence on biological systems (Albertini & Rustichelli 1993;Erdogan et al 2006;Hur Munawar et al 2013;Pamplona 2008;Schneider 2009;Stark 1991;Van der Paal et al 2016). The understanding of such mechanisms is vital, because liposomes represent a good model in the study of the effect of radiation on food, cells as well as sterilization of drug carriers.…”
Section: Introductionmentioning
confidence: 99%